A vertical channel model of molecular communication and its test-bed - Lu, Pengfei; Wu, Zhenqiang; Liu, Bo (EAI Endorsed Transactions on Pervasive Health and Technology, 2017)
The study of molecular communication is more and more prevalence, and channel model of molecular communication plays an important role in the molecular communication system. Diﬀerent propagation environment and modulation techniques lead to diﬀerent channel model, and most of the previous researches are mainly concentrate on the channel model in horizontal direction. However, in nature the communications between nano-machines are in short range and some of the information propagation are in the vertical direction, such as transpiration of plants, biological pump in ocean, etc. Therefore, in this paper a vertical channel model was proposed in which nano-machines communicate with each other mainly through diﬀusion at the vertical direction. Firstly, proposing a vertical molecular communication model, we mainly focus on the gravity, though the channel model is also aﬀected by other main factors, such as the ﬂow of the medium, the distance between the transmitter and the receiver, the delay or sensitivity of the transmitter and the receiver, etc. Secondly, we set up a test-bed for the vertical channel model, and verify the diﬀerences between the theoretical result and the experimental result. Finally, we get the parameters of the channel model which was proposed for the test-bed by utilizing the experimental data and the non-linear least squares method.
Keywords: Gravity; molecular communication; non-linear least squares method; test-bed; vertical channel model